2007
DOI: 10.1002/ccd.21079
|View full text |Cite
|
Sign up to set email alerts
|

Catheter‐directed thrombolysis (intrathrombus injection) in treatment of deep venous thrombosis: A systematic review

Abstract: Methods of delivery of thrombolytic agents for massive or limb threatening deep venous thrombosis (DVT) include a systemic infusion, local-regional administration, and catheter-directed therapy (tip of catheter placed inside the thrombus). We evaluated the effectiveness of catheter-directed therapy and compared the results with randomized clinical trials of systemic and local-regional thrombolytic therapy. Many who used catheter-directed thrombolysis used balloon angioplasty, stents, or thrombectomy in additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 24 publications
0
57
0
Order By: Relevance
“…Enden et al (2009) performed an RCT and showed that CDT combined with anticoagulant therapy significantly improved the rate of iliac and femoral vein patency over anticoagulant therapy alone. The number of published RCTs of CDT increased as European and American experts on the treatment of DVT rigorously evaluated the efficacy of CDT, and meta-analyses and systematic reviews of this topic have also been published (Janssen et al, 2005;Alesh et al, 2007;Vedantham, 2010). The results of these analyses have confirmed the efficacy of CDT, and Vedantham (2010) went so far as to state that CDT should be the preferred treatment for acute iliofemoral venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Enden et al (2009) performed an RCT and showed that CDT combined with anticoagulant therapy significantly improved the rate of iliac and femoral vein patency over anticoagulant therapy alone. The number of published RCTs of CDT increased as European and American experts on the treatment of DVT rigorously evaluated the efficacy of CDT, and meta-analyses and systematic reviews of this topic have also been published (Janssen et al, 2005;Alesh et al, 2007;Vedantham, 2010). The results of these analyses have confirmed the efficacy of CDT, and Vedantham (2010) went so far as to state that CDT should be the preferred treatment for acute iliofemoral venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Carefully selected patients with low bleeding risk (often younger patients) with extensive proximal iliofemoral DVT may benefit from thrombolysis, particularly CDT, in which bleeding rates are lower than the systemic thrombolytic therapy [143][144][145][146]. CDT should be considered for patients with symptomatic iliofemoral DVT who have symptoms of less than 14-day duration, good functional status, a life expectancy of 1 year or more and a low risk of bleeding.…”
Section: ) Compression Therapymentioning
confidence: 99%
“…23,25,26,29,30 Indeed, catheter-directed therapy is gaining in acceptance for the treatment of deep vein thrombosis of the extremities. 29,30 However, there has been no trial comparing catheter-directed therapy versus systemic tPA.…”
Section: Systemic Versus Catheter-administered Tissue Plasminogen Actmentioning
confidence: 99%
“…23,25,26,29,30 Indeed, catheter-directed therapy is gaining in acceptance for the treatment of deep vein thrombosis of the extremities. 29,30 However, there has been no trial comparing catheter-directed therapy versus systemic tPA. The use of catheter-directed therapy has also been emphasized with respect to Budd-Chiari syndrome, and it has been claimed that systemic thrombolytic therapy is not effective for this condition, based on two out of three patients who did not respond.…”
Section: Systemic Versus Catheter-administered Tissue Plasminogen Actmentioning
confidence: 99%
See 1 more Smart Citation